A Bioactive Carbon Nanotube‐Based Ink for Printing 2D and 3D Flexible Electronics. Issue 17 (24th February 2016) - Shin, Su Ryon; Farzad, Raziyeh; Tamayol, Ali; Manoharan, Vijayan; Mostafalu, Pooria; Zhang, Yu Shrike; Akbari, Mohsen; Jung, Sung Mi; Kim, Duckjin; Comotto, Mattia; Annabi, Nasim; Al‐Hazmi, Faten Ebrahim; et al.
Abstract : The development of electrically conductive carbon nanotube‐based inks is reported. Using these inks, 2D and 3D structures are printed on various flexible substrates such as paper, hydrogels, and elastomers. The printed patterns have mechanical and electrical properties that make them beneficial for various biological applications.